Semiotic analysis of the film Parasite - Mozharova, Anastasiia; Sigmund, Tomáš; Korčák, Jiří, 1994-; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2022)
This bachelor thesis is focused on the semiotic analysis of the film Parasite and aims to identify unique signs of the film that reflect South Korean culture and inequality in society while simultaneously analyzing their role in the plot. The purpose of the work is to analyze the demonstration of different classes in society and to understand if the cultural signs of the film have an impact on the perception of the essence of the film - who is the parasite? The work is divided into two parts, a theoretical part, and a practical part. The theoretical part focuses on the basic semiotic theories and their further development in cinema, as well as explaining the main aspects that make up the film, such as structure and characters. In the practical part, there is an outline of South Korean cinema, the analysis of Bong Joon-ho’s film culture, and the film Parasite itself, more specifically the plot, the characters, and finally the signs themselves. The final part of the work answers the question of the director's originality and talks about the reason for his success, as well as the possible impact on the future of cinema.
Vedoucí práce: Tomáš Sigmund
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: multimédia v ekonomické praxi [obor bakal. práce]; bakalářské práce; bachelor's theses